2018
DOI: 10.1113/jp276011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of movement‐related pain on behaviour and corticospinal excitability changes associated with arm movement preparation

Abstract: When a movement repeatedly generates pain, we anticipate movement-related pain and establish self-protective strategies during motor preparation, but the underlying mechanisms remains poorly understood. The current study investigated the effect of movement-related pain anticipation on the modulation of behaviour and corticospinal excitability during the preparation of arm movements. Participants completed an instructed-delay reaction-time (RT) task consisting of elbow flexions and extensions instructed by visu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 72 publications
1
30
1
Order By: Relevance
“…With regard to reaction time, studies investigating movement-related experimental pain in humans have shown both shorter and prolonged reaction times (Misra et al 2017a;Neige et al 2018). In the current study we found longer reaction times in the cLBP+ group, perhaps as a result of an increase in endogenous movement-evoked pain.…”
Section: Figure 4 Time-frequency Representations Of Premotor and Smentioning
confidence: 99%
“…With regard to reaction time, studies investigating movement-related experimental pain in humans have shown both shorter and prolonged reaction times (Misra et al 2017a;Neige et al 2018). In the current study we found longer reaction times in the cLBP+ group, perhaps as a result of an increase in endogenous movement-evoked pain.…”
Section: Figure 4 Time-frequency Representations Of Premotor and Smentioning
confidence: 99%
“…Neige et al. provide new evidence of how the anticipation of movement‐related pain alters corticospinal tract excitability during motor preparation (Neige, Mavromatis, Gagné, Bouyer, & Mercier, ). They recorded motor evoked potentials from the biceps brachii immediately preceding the execution of elbow flexion and extension movements.…”
mentioning
confidence: 99%
“…In contrast, several previous studies reported that healthy participants performed movements quickly under the experimental condition of feeling fear 27,34 . We suspect that these differences in results between previous investigations and our present study are due to the timing of the delivery of the painful stimulation.…”
Section: Discussionmentioning
confidence: 60%